Exploiting the Potential of Bioactive Molecules Extracted by Ultrasounds from Avocado Peels-Food and Nutraceutical Applications - Beatriz Rodríguez-Martínez; Pedro Ferreira-Santos; Beatriz Gullón; José António Teixeira; Cláudia M. Botelho; Remedios Yáñez (MDPI AG, 2021)
Natural bioactive compounds from food waste have fomented interest in food and pharmaceutical industries for the past decade. In this work, it purposed the recovery of bioactive avocado peel extract using an environmentally friendly technique: the ultrasound assisted extraction. The response surface methodology was applied in order to optimize the conditions of the extraction, ethanol-water mixtures and time. The optimized extracts (ethanol 38.46%, 44.06 min, and 50 °C) were chemically characterized by HPLC-ESI-MS and FTIR. Its antioxidant ability, as well as, its effect on cell metabolic activity of normal (L929) and cancer (Caco-2, A549 and HeLa) cell lines were assessed. Aqueous ethanol extracts presented a high content in bioactive compounds with high antioxidant potential. The most representative class of the phenolic compounds found in the avocado peel extract were phenolic acids, such as hydroxybenzoic and hydroxycinnamic acids. Another important chemical group detected were the flavonoids, such as flavanols, flavanonols, flavones, flavanones and chalcone, phenylethanoids and lignans. In terms of its influence on the metabolic activity of normal and cancer cell lines, the extract does not significantly affect normal cells. On the other hand, it can negatively affect cancer cells, particularly HeLa cells. These results clearly demonstrated that ultrasound is a sustainable extraction technique, resulting in extracts with low toxicity in normal cells and with potential application in food, pharmaceutical or nutraceutical sectors.